A review on the bioactive compounds of Rhus chinensis Mill. native to the Sikkim Himalayas - Banerjee, Sujan; Bhupendra Shrestha; Surabhi Mandal (Journal of Applied Pharmaceutical Research, 2025)
Background: The Sikkim Himalaya is home to the wild medicinal shrub Rhus chinensis Mill, which produces edible fruits. Traditionally, the fruit juice concentrate has been used to treat a variety of stomach issues. The plant is rich in phytoconstituents, including gallic acid (up to 130.4 ± 2.5 mg/g), methyl gallate, flavonoids, and tannins, which contribute to its traditional applications in managing conditions such as diarrhoea, dysentery, toothache, cough, and wounds. The total flavonoids and flavonol levels were quantified as rutin equivalents. The total phenolics were calculated as gallic acid equivalents. Through various in vitro antioxidant methods, including DPPH, Total antioxidant content, ABTS, and Hydrogen peroxide scavenging assays, the antioxidant capacity was determined.  Methodology: This review combines data from numerous research studies and review articles that have elaborated on the various phytoconstituents, medicinal uses, and pharmacological properties of different Rhus species. Results and Discussion: This review provides a detailed description of multiple phytoconstituents, traditional uses, and medicinal applications of Rhus species. The quantitative findings from previous studies report the total phenolic content as 123.52±1.29 mg GAE/g. IC50 values through DPPH free radical scavenging assay and Hydrogen scavenging assay were  42.69±0.1% and 63.20±1.48% respectively. Conclusion: This review provides an in-depth description of various phytoconstituents, including gallic acid, citric acid, myricetin-3-O-rhamnoside, methyl gallate, quercetin-3-O-arabinoside, and protocatechuic acid, among others. These results provide concrete evidence to support the potential of Rhus chinensis Mill. as a source of bioactive compounds for the creation of new treatments.